Implementasi e-commerce untuk meningkatkan daya saing pelaku Industri Kecil Menengah (IKM) bidang Agro Binaan Dinas Perindustrian dan Perdagangan Kabupaten Malang - Vion Age Tricahyo; Fatra Nonggala Putra; Gleydis Harwida; Fasta Della Fitrotul Husnayaini; Pipit Lailatul Rahmania (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2022)
Small and medium enterprises (SME) are one of the biggest economic contributors to Indonesia. Through the abundant product potential and 64.19 million people involved, a solution is needed to increase income. Digital marketing implementation using e-commerce is the best way. To make this happen, researchers collaborate with the Department of Industry and Trade of Malang Regency. With the division unit, namely IKM Agro, training on e-commerce implementation was made to increase the competitiveness of 270 IKM which had made 400 products. IKM Agro assisted products already have attractive packaging, product standardization and halal certification. However, some products have less selling power because they still use conventional sales such as exhibitions and shops. The purpose of this service is to maximize the role of SME actors by implementing product sales through e-commerce. And make the products of SME actors able to reach millions of Indonesian customers and international markets. With this activity, 88% of SMEs benefit from the use of marketing technology as an effort to increase income and improve product competitiveness.